Surface composition, structure and corrosion properties of a ZrTiNb alloy: Effect of impact treatment energy. (April 2023) - Chenakin, S.P.; Mordyuk, B.N.; Khripta, N.I.
Abstract: A comparative study of the microstructure, surface chemical and phase composition, microtopography, surface roughness, microhardness, and corrosion properties of Zr31Ti18Nb alloy in as-prepared state and after ultrasonic impact treatment under two loading schemes has been carried out by using XRD, XPS, SEM/EDX and TEM/SAED. The surface of as-prepared alloy was considerably enriched with Zr as compared to the nominal composition, covered by a thick native oxide and comprised carbide and nitride precipitates. The processing of the alloy for 2 min in (i) a multi-pin impacting mode combined with a reciprocating movement of the sample and (ii) single-pin normal impacting mode caused deformation-enhanced uptake of oxygen promoting further oxidation of the alloy components. Besides, the impact treatment brought about the accumulation of structural defects, texturing, generation of compressive residual stresses, a decrease in surface roughness, an increase in microhardness, and a significant increase in the corrosion resistance of the alloy in a 0.9% NaCl solution. The highest effect of surface modification of the alloy was obtained after treatment in the single-pin impacting mode. This was related to a larger energy density and power density deposited in the impact area during processing in this mode as evaluated from measurements of pins' energetics. Highlights: Impact treatment of a Zr–31Ti–18Nb alloy under two loading schemes. Deformation-enhanced oxidation of the alloy components and carbide/nitride precipitates under both loading modes. Increase in microhardness, a decrease in surface roughness and texturing in the impact-treated alloy. Significant increase in the corrosion resistance of the impact-treated alloy in a 0.9% NaCl solution. Single-pin normal impact mode provides a stronger surface modification than multi-pin sliding impact mode.